2018
DOI: 10.1038/s41598-018-31079-0
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of key genes affecting artemisinin content in five Artemisia species

Abstract: Artemisinin, an effective anti-malarial drug is synthesized in the specialized 10-celled biseriate glandular trichomes of some Artemisia species. In order to have an insight into artemisinin biosynthesis in species other than A. annua, five species with different artemisinin contents were investigated for the expression of key genes that influence artemisinin content. The least relative expression of the examined terpene synthase genes accompanied with very low glandular trichome density (4 No. mm−2) and absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…To eliminate the environmental effects, the plants were propagated under the same conditions. Eliminating environmental effects via plant propagation under the same conditions have been noted by others studies [42,52,56]. In the current study, the presence of three different isoforms in the Allium was discovered for the first time.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…To eliminate the environmental effects, the plants were propagated under the same conditions. Eliminating environmental effects via plant propagation under the same conditions have been noted by others studies [42,52,56]. In the current study, the presence of three different isoforms in the Allium was discovered for the first time.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…In addition to the complexity of the biosynthetic route, genes expression levels and enzyme activities also affect the allicin contents. Most studies have shown a close relationship between metabolome and genes expression levels [51,52,55,57,58,59,60]. The results showed that the expression patterns of isoforms were variable among different tissues in Allium species (Fig 5).…”
Section: Conclusion and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In vitro culture of hazel ( Corylus avellana , European filbert) has been made known as a promising and inexpensive strategy for producing paclitaxel ( Gallego et al, 2017 ; Salehi et al, 2017 ; Salehi et al, 2018c ; Salehi et al, 2019b ; Salehi et al, 2019c ; Farhadi et al, 2020 ; Salehi et al, 2020 ). Biosynthesizing bioactive compounds in plants is influenced by various factors ( Torkamani et al, 2014 ; Salehi et al, 2017 ; Salehi et al, 2018a ; Salehi et al, 2018b ; Salehi et al, 2018c ; Salehi et al, 2019a ; Salehi et al, 2019b ; Salehi et al, 2019c ; Salehi et al, 2019d ). Previous studies ( Salehi et al, 2019b ; Salehi et al, 2019c ; Farhadi et al, 2020 ; Salehi et al, 2020 ) demonstrated the positive influences of cell extract (CE) and culture filtrate (CF) of endophytic fungi on paclitaxel biosynthesis in cell suspension culture (CSC) of C. avellana .…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining highproducing cell cultures is essential for producing secondary metabolites by way of plant in vitro culture [15]. Biosynthesizing bioactive compounds in plants are influenced by various factors [6][7][8][16][17][18][19]. Fungal elicitors including cell extract (CE) and culture filtrate (CF) have been described as an impressive strategy for improving paclitaxel biosynthesis in cell suspension culture (CSC) of C. avellana [6,7,[10][11][12][13].…”
mentioning
confidence: 99%